2000
DOI: 10.1080/03014223.2000.9518228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of season, habitat, temperature, and invertebrate availability on nocturnal activity of the New Zealand long‐tailed bat (Chalinolobus tuberculatus)

Abstract: Nocturnal patterns of activity by the New Zealand long-tailed bat (Chalinolobus tuberculatus) varied significantly in relation to habitat, season, time of night, temperature, and invertebrate activity. Automatic bat detection units recorded 12072 bat passes containing 593 feeding buzzes during 580 nights of sampling. Overall, 46.3% of passes were along roads within forest, 42.7% along forest edges, 8.1% in open grassland and 2.9% within forest. Pass rates averaged 30.8/night (95% confidence interval (CI) = 23.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 43 publications
6
68
1
3
Order By: Relevance
“…They are typical aerial insectivores that primarily forage along forest edges and along roads within forest after leaving their roosts at dusk. They feed throughout the night, but the extent of their foraging activity is influenced by such factors as season, temperature, and availability of flying insects (Griffiths 1996;Sedgeley & O'Donnell 1999a,b;O'Donnell 2000bO'Donnell , 2005Alexander 2001;Moore 2001). In contrast, little is known about lesser short-tailed bats' habitat requirements or temporal patterns of activity beyond the general observation that they are usually associated with large expanses of mature indigenous forest (Daniel 1976(Daniel ,1979Daniel & Williams 1984;Arkins et al 1999;Lloyd 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are typical aerial insectivores that primarily forage along forest edges and along roads within forest after leaving their roosts at dusk. They feed throughout the night, but the extent of their foraging activity is influenced by such factors as season, temperature, and availability of flying insects (Griffiths 1996;Sedgeley & O'Donnell 1999a,b;O'Donnell 2000bO'Donnell , 2005Alexander 2001;Moore 2001). In contrast, little is known about lesser short-tailed bats' habitat requirements or temporal patterns of activity beyond the general observation that they are usually associated with large expanses of mature indigenous forest (Daniel 1976(Daniel ,1979Daniel & Williams 1984;Arkins et al 1999;Lloyd 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Long-tailed bats have been studied in the same area since 1993, and their temporal patterns of activity have been reported elsewhere (O'Donnell 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…Other research into long-tailed bats in Kinleith Forest found they were detected more commonly along roads among P. radiata which were near harvest age, and that bat activity along a road in one area of P. radiata exceeded that along the same road where it passed through a nearby indigenous remnant (Moore 2001). Nevertheless, rates of detection of bats in Kinleith Forest were far lower than in comparable bat detector-based research in the native Nothofagus forest of Fiordland's Eglinton Valley (O'Donnell 2000a;Borkin & Parsons 2009), and whilst no direct relationship has yet been established between detection rates and actual numbers of bats present (Parsons 2001), we presume that this indicates a smaller population in Kinleith Forest.…”
Section: Long-tailed Bat Research In Plantation Forestmentioning
confidence: 86%
“…Torpor is especially important in cold weather (Webb 1999;O'Donnell 2000a) because it reduces the energy expenditure required to maintain life (Speakman & Thomas 2003), but it may be used during the day even in summer (Turbill et al 2003). The metabolic state of torpid bats is reduced, and correspondingly also their ability to breathe, move (Speakman & Thomas 2003) and escape when their roost tree is felled.…”
Section: Current Knowledge Of the Effect Of Logging On Long-tailed Batsmentioning
confidence: 99%
See 1 more Smart Citation